Effect of diclofenac on the production of volatile fatty acids from anaerobic fermentation of waste activated sludge. (April 2018) - Hu, Jiawei; Zhao, Jianwei; Wang, Dongbo; Li, Xiaoming; Zhang, Dan; Xu, Qiuxiang; Peng, Lai; Yang, Qi; Zeng, Guangming
Graphical abstract: Highlights: Diclofenac facilitated VFAs production from sludge anaerobic fermentation. A significant level of diclofenac was degraded in the fermentation process. Diclofenac promoted acidogenesis, acetogenesis, and homoacetogenesis processes. Diclofenac inhibited methanogenesis process. Abstract: In this study, the impact of diclofenac (DCF), an antiinflammatory drug being extensively used in human health care and veterinary treatment, on the production of volatile fatty acids (VFAs) from anaerobic fermentation of waste activated sludge (WAS) was investigated for the first time. Experimental results showed that when DCF concentration increased from 2.5 to 25 mg/kg total suspended solid (TSS), the maximum production of VFAs increased from 599 to 1113 mg COD/L, but further increase of DCF to 47.5 mg/kg TSS decreased VFAs yield to 896 mg COD/L. The mechanism investigation revealed that DCF had no effect on the hydrolysis process, promoted the process of acidogenesis, acetogenesis, and homoacetogenesis, but severely inhibited methanogenesis, leading to the accumulation of VFAs. Microbial community analysis showed that the addition of DCF could promote the relative abundance of VFAs (especially acetic acid) producers, which was well consistent with the results obtained above.